PENGARUH KEBIASAAN MENCUCI TANGAN DAN KETERSEDIAAN AIR BERSIH DENGAN CACINGAN PADA MURID SEKOLAH DASAR KECAMATAN DELIMA KABUPATEN PIDIE TAHUN 2025 - Maifrizal Maifrizal; Muhammad Shalahuddin; Dara Maulida; Wahidanur Wahidanur; Khairol Razi (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2025)
Worm infestation in children can lead to a lack of abilities due to a lack of iron, a lack of macronutrients, slowing down children's physical growth, development, and activity and intelligence. The purpose of this study was to determine the effect of handwashing and the availability of clean water on the incidence of worms in elementary school students in Delima District, Pidie Regency in 2025. This study was analytical with a cross-sectional study design. The population and sample in this study were 79 students from grades 4 to 6. The sampling technique was total sampling. This study was conducted on June 30 - July 4, 2025. Data collection was carried out using a questionnaire. The results of the univariate test showed that the majority of students did not experience worms (88.6%), the majority of students had the habit of washing their hands (87.3%), and the majority of students had clean water available (91.1%). Bivariate tests revealed a relationship between handwashing habits and worm infestation (P=0.000), and no relationship between clean water availability and worm infestation (P=0.961). Students are advised to increase their awareness and practice of handwashing with soap, as well as maintaining personal and environmental hygiene. Students also need to understand that hand hygiene and the use of clean water are simple yet crucial steps to prevent worm infestation and other diseases